2023
DOI: 10.1088/1361-6463/acbbda
|View full text |Cite
|
Sign up to set email alerts
|

An optically transparent flexible metasurface absorber with broadband radar absorption and low infrared emissivity

Abstract: The rapid development of surveillance technology has driven the research of multispectral stealth. Demand for infrared and microwave radar compatible stealth is becoming increasingly urgent in military applications. Herein, a versatile metamaterial absorber is designed and fabricated to simultaneously achieve ultra-broadband radar scattering reduction, low infrared emission, and high optical transparency. The designed structure consists of an infrared stealth layer, radar absorption layers, and backing ground.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It can be found that the IR radiation of the checkerboard metasurface is higher than the metal plate, but is significantly lower than PET, which confirms the good IR stealth performance of the metasurface. Based on the imaging results, it can be estimated that the IR emissivity of the checkerboard metasurface is as follows [ 39 ]: where is the temperature displayed in the IR image, is the ambient temperature of the metasurface, and is the atmospheric temperature. The ambient temperature is 50 °C, the atmospheric temperature is 25 °C, and the checkerboard metasurface in Figure 13 c shows a temperature of about 32 °C.…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the IR radiation of the checkerboard metasurface is higher than the metal plate, but is significantly lower than PET, which confirms the good IR stealth performance of the metasurface. Based on the imaging results, it can be estimated that the IR emissivity of the checkerboard metasurface is as follows [ 39 ]: where is the temperature displayed in the IR image, is the ambient temperature of the metasurface, and is the atmospheric temperature. The ambient temperature is 50 °C, the atmospheric temperature is 25 °C, and the checkerboard metasurface in Figure 13 c shows a temperature of about 32 °C.…”
Section: Experimental Validationmentioning
confidence: 99%
“…It can be found that the IR radiation of the checkerboard metasurface is higher than the metal plate, but is significantly lower than PET, which confirms the good IR stealth performance of the metasurface. Based on the imaging results, it can be estimated that the IR emissivity of the checkerboard metasurface is as follows [39]:…”
Section: Experimental Validationmentioning
confidence: 99%
“…The differences in the IR emissivity at different positions in Figure 9b,c were caused by inhomogeneous heating. The IR emissivity of the IRSL can be approximately estimated by [42] e IRSL = (T…”
Section: Experimental Verificationmentioning
confidence: 99%